Spiritualitas dan Kesehatan Mental pada Penyintas COVID-19 - Lindasari, Sri Wulan; Nuryani, Reni; Lindayani, Emi; Sukaesih, Nunung Siti; Sopiah, Popi (Faletehan Health Journal, 2024)
The COVID-19 pandemic can affect not only the physical but also mental health of the survivors. Particularly, mental health problems may influence their emotional, cognitive, physical, and social aspects. Meanwhile, one of the factors that closely relate to the problems is spirituality. This study aimed to determine the relationship between spirituality and mental health in COVID-19 survivors. The type of the research was descriptive correlation. The research respondents totaled 100 COVID-19 survivors. The sampling technique used simple random sampling. To collect the data, The Daily Spiritual Experience Scale (DSES) was utilized to measure spirituality and The Mental Health Continuum-Short Form (MHC-SF) to measure mental health. The results showed that the majority of respondents had a high level of spirituality (52%) and a good mental health (64%). The chi-square test results obtained a P value of 0.003, which means there was a significant relationship between spirituality and mental health in COVID-19 survivors. This research showed that the higher the spirituality, the better the mental health of COVID-19 survivors.